2012
DOI: 10.5740/jaoacint.10-407
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Natural Pesticides in Fresh Fruits Using Liquid Chromatography/Mass Spectrometry

Abstract: An analytical procedure was developed for the determination of some natural pesticides (piperonyl butoxide, nicotine, rotenone, spinosad, and abamectin B1a) in fruit matrixes. The quick, easy, cheap, effective, rugged, and safe (QuEChERS) method was used for extraction. Analysis of the extract was performed by LC-electrospray ionization (ESI)-MS/MS. The ions prominent in the ESI spectra were [M+Na]+ for abamectin B1a, [M+NH4]+ for piperonyl butoxide, and [M+H]+ for the rest of the compounds. A Zorbax SB-C18 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Several approaches to determine pesticide residues in citrus fruit and processed citrus products, such as fruit soft drinks, , juices, , and essential oils, , have been developed. The most notable is the QuEChERS method and its different versions, , as well as the ethyl acetate method .…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches to determine pesticide residues in citrus fruit and processed citrus products, such as fruit soft drinks, , juices, , and essential oils, , have been developed. The most notable is the QuEChERS method and its different versions, , as well as the ethyl acetate method .…”
Section: Introductionmentioning
confidence: 99%
“…The method was linear within the investigated concentration range, displaying a calibration curve correlation factor of 0.99. The CVs obtained were below 20%, and recoveries were in the 70-110% range [35]. This paper describes a method for the sensitive and selective determination of two macrocyclic lactones (abamectin and spinosad) and azadirachtin in apple purée, concentrated lemon juice, tomato purée and canned peas.…”
Section: Ultimately We Have To Go For Natural Biopesticidesmentioning
confidence: 99%
“…It was found that ascorbic acid stabilized labile pesticides and showed valid performance data. Ruiz et al (2012) developed an analytical procedure for the determination of some natural pesticides (piperonyl butoxide, nicotine, rotenone, spinosad and abamectin Bla) in fruit matrices.…”
mentioning
confidence: 99%